Micro-Factory: A Small Factory to Manufacture Even Smaller Parts - Shukla, Mr Abhishek; Singh, Gaurav (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
A micro-factory is best described as a small factory to manufacture even smaller parts. The precision of the control mechanism and the required accuracy by each of its tools has made micro-factory an interesting topic for research and development. The introduction of automatic control, the use of visual feedback, the development of novel control algorithms for motion control are a few fields which gives a lot of scope for researchers to explore.